Amurensin H, a Derivative From Resveratrol, Ameliorates Lipopolysaccharide/Cigarette Smoke–Induced Airway Inflammation by Blocking the Syk/NF-κB Pathway - Fan, Yannan; Zhang, Ziqian; Yao, Chunsuo; Bai, Jinye; Yang, Hui; Ma, Pei; Fan, Yiyao; Li, Shuyi; Yuan, Jiqiao; Lin, Mingbao; Hou, Qi (Frontiers in Pharmacology, 2019)
Amurensin H, a resveratrol dimer derived from Vitis amurensis Rupr, has several biological effects, including anti-inflammatory and anti-oxidant activities. Studies have found that amurensin H attenuated asthma-like allergic airway inflammation. However, its protective activity on COPD airway inflammation are not fully explored. The present study used a lipopolysaccharide/cigarette smoke (LPS/CS) -induced mice model and a lipopolysaccharide (LPS)-stimulated THP-1-derived macrophages model to measure the lung tissue’s morphology changes. The results showed that amurensin H ameliorated the histological inflammatory alterations in the lung tissues, led to a decrease in the expression of interleukin (IL)-6, IL-17A, TNF-α, and IFN-γ in bronchoalveolar lavage fluid (BALF). Amurensin H also significantly inhibited the release of IL-1β, IL-6, IL-8 and TNF-α in LPS-stimulated THP-1-derived macrophages. Furthermore, amurensin H markedly inhibited the expressions of p-Syk, NF-κB and p-NF-κB both in vivo and in vitro. Results from co-treatment with Syk inhibitor BAY61-3606 and NF-κB inhibitor BAY11-7082 in vitro revealed that amurensin H’s protective effect against airway inflammation could be due partly to the inhibition of the Syk/NF-κB pathway. These findings suggest that amurensin H shows therapeutic effects on COPD airway inflammation, and inhibiting the Syk/NF-κB pathway might be part of its underlying mechanisms.